(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Pasaru F, Yunus M, Toana MH, Edy N, Anshary A, Saleh S. 2021. Incidence of banana leaf roller and diversity of it is parasitoids in Central Sulawesi, Indonesia. Biodiversitas 22: 5023-5029. Incidence of banana leaf roller and diversity of it is parasitoids in Central Sulawesi, Indonesia. Indonesia is still facing banana losses due to the leaf roller (Erionota thrax). Fortunately, it has several natural enemies potentially to control them. Therefore, a survey was done to measure the incidence of banana leaf roller (BLR) at different altitudes and banana cultivars as well as the diversity and parasitism of its parasitoids. The pra-imago stages of BLR were collected at different altitudes and banana cultivars in Central Sulawesi, Indonesia, and transported to the laboratory for rearing and parasitism observation. The study revealed that the incidence of E. thrax in the surveyed locations varied from 28.6% to 85.8%, whereas the parasitism level of the BLR parasitoids was 0.0 to 22.1%. Incidence of E. thrax tended to be higher at a higher altitude while Kepok cultivar seemed to be less prone to BLR infestation compared with Raja and Mas cultivars. A total of nine parasitoids of BLR were recorded. They were Agiommatus sumatraensis, Pediobius erionotae, Ooencyrtus pallidipes, Brachymeria lasus, Brachymeria thracis, Cotesia erionatae, Xanthopimpla gampsura, Casinaria sp, and Palexorista solennis. Among them, B. lasus was the most abundant, widely distributed, and had the highest parasitism rate. Our study figured out that BLR infestation is a major problem in Central Sulawesi. Nevertheless, the presence of parasitoids recorded in this study may potentially be used as the biological control.